Development of autoimmune thyroid disease after COVID-19 infection: case report - Du, Si-na; Chen, Jian-wei; Li, Wei; Wang, Meng-chuan; Mao, Yu-shan (Frontiers in Medicine, 2024)
Background: SARS-CoV-2 could trigger multiple immune responses, leading to several autoimmune diseases, including thyroid diseases. Many cases of thyroid diseases caused by COVID-19 infection have been reported. Here, we describe the disease development of patients with autoimmune thyroid disease after COVID-19 infection. Methods: The clinical characteristics, diagnosis and treatment of five different patients with autoimmune thyroid disease after COVID-19 infection were reported. Results: Female patients with primary autoimmune thyroid disease which have been stable for many years were reported. One month after COVID-19 infection, the disease has undergone different evolution. Case 1, a patient with history of long-term stable Hashimoto's thyroiditis, suddenly suffered from Graves disease after COVID-19 infection. Case 2, a patient with history of long-term stable Hashimoto's thyroiditis with thyroid nodules, suddenly suffered from Graves disease after infection. Case 3, a patient with history of long-term stable Graves disease, suddenly suffered from worsening after infection. The above three cases showed thyroid-stimulating antibodies were enhanced. Case 4, a patient with history of previous hypothyroidism had an increase in thyroid-related antibody (TPOAb and TRAb) activity after infection, followed by a marked worsening of hypothyroidism. Case 5, a patient with no history of thyroid disease suddenly developed controllable "thyrotoxicosis" after infection, suggesting the diagnosis of painless thyroiditis.The five case reports show a different development of the primary autoimmune thyroid disease after COVID-19 infection. The change in the trend of thyroid disease is closely related to the immune response induced by SARS-CoV-2 infection.